Subjective perception of anxiety as PSYCHOSOCIAL effect of COVID-19 - Robak, Magdalena; Jurkiewicz, Beata (Journal of Education, Health and Sport, 2022)
Introduction: Every day, people are more or less anxious, but during the SARS-CoV-2 pandemic, this anxiety can be greatly exacerbated. The aim of this study was to analyze the subjective feelings of anxiety associated with being in quarantine due to infection or suspected infection with SARS-CoV-2. Material and methods: The study included 138 people from different backgrounds. It was conducted using a survey (Google Form) consisting of fifteen questions. Results were compiled using chi2, Kendall’s tau-b, one-way ANOVA analysis of variance with Bonferroni post hoc tests. Results: The level of experienced anxiety during the quarantine by the subjects was found to be statistically significantly higher compared to its level before and after the quarantine period (p=0.002). An increase in somatic symptoms was also observed during isolation (29.0%). Statistical analysis, however, confirmed the relationship between the sex of the subjects and the level of anxiety during and after quarantine (p<0.05) - women experienced anxiety slightly more strongly. In addition, younger people experienced higher levels of anxiety before quarantine than older people (p=0.001). The study also showed that some subjects felt the need to take sedatives (29.0%) and/or seek psychological/psychotherapeutic help (38.4%) during or after quarantine. Conclusions: Being in forced isolation has an impact on the severity of anxiety and the maintenance of high anxiety levels even after quarantine is over. These results show the importance of monitoring mental health during (and in relation to) a pandemic.